HERVd: the Human Endogenous RetroViruses Database: update - Pačes, Jan (Oxford University Press, 2004)
An elaboration of HERVd (http://herv.img.cas.cz) is being carried out in two directions. One of them is the integration and better classification of families that diverge considerably from typical retroviral genomes. This leads to a more precise identification of members with individual families. The second improvement is better accessibility of the database and connection with human genome annotation.